Use of n-Butyl 2 Cyanoacrylate without Lipiodol, Using a Modified Protocol in Gastric Variceal Bleed Management: Retrospective Analysis of 2299 Patients - Desai, Pankaj N.; Patel, Chintan N.; Kabrawala, Mayank V.; Mehta, Rajiv M.; Nandwani, Subhash K.; Prajapati, Ritesh; Patel, Nisharg; Parekh, Krishna K. (Journal of Digestive Endoscopy, 2020)
Aim To assess the feasibility and amount of cyanoacrylate glue that can be injected safely per session, complications, and long-term results in GOV1, GOV2 and IGV1 varices, using a modified method.Method All patients from October 2008 to December 2019 presenting to us with variceal bleeding were included. We injected 0.5 mL of cyanoacrylate glue followed by 1.5 mL to 3 mL distilled water in all GOV 1, GOV 2 and IGV varices. Number of glues used were not restricted. Esophageal variceal ligation (EVL) was done for esophageal varices. Follow-up was done at 4 weeks and 3 to 6 months and analyzed.Results 2299 patients received therapy. Male:female, 69%:31%. Causes of varices–cirrhosis (84.9%) and extrahepatic portal vein obstruction (EHPVO) (15.1%). Causes of cirrhosis–alcohol (38.4%), nonalcoholic fatty liver disease (NAFLD) (29%), hepatitis B (19.9%), hepatitis C (10.1%), Wilson’s disease (1.8%), and autoimmune diseases (0.9%). As much as 41.1% had blood in stomach and 10.2% had active spurt on index endoscopy. As much as 14.5% required endotracheal intubation (active bleed [53.1%], encephalopathy [40.5%], respiratory distress [6.6%]). As much as 30.9% had GOV1 + GOV2, 1.5% had GOV2 + IGV1, 21.3% had GOV1 + IGV1 and 16.4% had GOV1 + GOV2 + IGV1. Hemostasis could be achieved in 99.2% on index endoscopy. A total of 18 (0.8%) patients had uncontrolled bleed of whom 10 (55.6%) had hepatocellular carcinoma. Ongoing bleed was treated with transjugular intrahepatic portosystemic shunt (TIPSS) (61.1%) and endoscopic ultrasound (EUS)-guided coiling (38.8%). Amount of glue required for gastric variceal obturation was 3.6 on index endoscopy, 1.6 on follow-up at 4 to 6 weeks, and 1.2 at 3 months follow up. Glue extrusion with ulcers were seen in 6.4% at 4 to 6 weeks and 4.3% at 3 months. Rebleed occurred in 2.1% and 0.7% patients before 4 weeks and 3 months follow-up, respectively. As much as 1.3% and 1.2% patients were lost to follow-up before 4 weeks and 3 months follow-up sessions, respectively. Complications include pulmonary aspiration in 0.9% and bleeding from ulcers 2.8%. No evidence of pulmonary embolism was seen. In two endoscopic procedures, glue splashing into operator’s eyes occurred. Incidents of needle getting stuck in the varix occurred in three patients.Conclusions Our modified protocol for glue in gastric varices is safe and feasible, as it has less rebleed, no pulmonary embolism and less ulcers with glue extrusion as compared with available literature.
Keywords: cyanoacrylate glue; gastric varices; variceal bleed